Rabbiteye blueberry (Vaccinium ashei Reade) propagation by cuttings - Hoffmann, Alexandre; Fachinello, José Carlos; dos Santos, Alverides Machado (Pesquisa Agropecuaria Brasileira, 1995)
Rabbiteye blueberry is a temperate fruit crop that shows good perspectives to commercial exploration. The troubles of vegetative propagation make difficult the expansion of rabbiteye. This experiment aimed to verify the IBA (indolbutyric acid) and antioxidants effect on rooting of cuttings collected at different times. Median cuttings of Powder Blue and Climax cultivars collected in November, March and August were utilized, kept in antioxidants treatments (destilled water and ascorbic acid) and after this, the cuttings were treated with IBA, powder formulation, at 0, 2000, 4000 and 6000 ppm. The cuttings were kept during 90 days under mist. Three replications were used with 9 cuttings each one. In November, greater rooting percentages (near 80% for Powder Blue and near 40% for Climax) and the best root growing were obtained. IBA affected rooting and root system development and the best results were obtained around 2000 and 4000 ppm. No effect of antioxidants treatments was observed upon annalysed variables, but they affected other factors effect.
Keywords: rooting; indolbutyric acid; antioxidant